Primary Cutaneous Actinomycosis Mimicking Cutaneous Leishmaniasis - Ratnakar R. Kamath; Mahendra M. Kura; Rituparna Basumatary (Wolters Kluwer Medknow Publications, 2023)
Actinomycosis is a chronic suppurative bacterial infection commonly seen in the tropics, caused by gram-positive, anaerobic bacilli of the genus Actinomyces. There are very few reported cases of primary cutaneous actinomycosis. It can mimic mycetoma, tuberculosis, nocardiosis, and botryomycosis. A high index of clinical suspicion is required for diagnosis in the absence of sinuses. Even with repeated attempts, cultures are mostly negative; and hence, histology reveals the diagnosis in most cases. Here, we report an unusual case of primary cutaneous actinomycosis in a 21-year-old female patient, following a road traffic accident (RTA). A positive Splendore-Hoeppli phenomenon and special stains demonstrated the ray fungus and helped us reach the diagnosis. The patient was started on oral penicillin G and showed good response.